An example of digital field training for a diversity-friendly (and pandemic-proof) field education in geoengineering disciplines. Issue 1 (1st January 2023) - Godlewska, J C; Ogan, M S; Duda, M; Backers, T
Abstract: Geological field training and site inspections are important components of the education in geological and civil engineering and associated disciplines. However, field training is not inclusive, does not consider students' family situations, for example associated with care work, places high demands on students' financial resilience, and therefore does not address family educational backgrounds. Also, it is not pandemic proof. Through the implementation of digital field training, students can get access to important aspects of field work in a barrier-reduced and location-independent way. Knowledge associated with geological field training therefore becomes more accessible and inclusive. Moreover, outcrops or specific rock structures that are difficult or unsafe to access in the field can be explored digitally. In this project, parts of a geological mapping course physically held in southern Germany and taught at the Faculty of Geosciences at Ruhr-Universität Bochum were turned into a digital field course. A virtual 360° tour with 3D models of outcrops and rock samples was complemented by photo, video and audio material with information on the geological setting. The digital field training was integrated via Moodle as a full lecture with H5P elements. Additionally, individual components were combined in a game engine, so that students can immerse themselves into the project settings via virtual reality experiences or on-screen. The learning outcome includes the creation of a geological map in the study area in QGIS that is complemented by a field report. The choice of equipment, procedure and results are presented. While acknowledging that a digital experience cannot fully replace the learning experience of physical field trips, it can be a valuable complement to physical field work, provide access to inaccessible geological regions, support interdisciplinary teaching projects, and provide an alternative to marginalised students who would otherwise not be able to complete a geoengineering curriculum.